1988
DOI: 10.1126/science.3051382
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Asp-Asp-Glu-Asp Can Inhibit Transport of Nuclear Proteins into the Nucleus

Abstract: The signal sequence of simian virus 40 (SV40) large T-antigen for translocation into the nucleus is composed of positively charged amino acids Lys-Lys-Lys-Arg-Lys. Rabbit antibodies to a synthetic peptide containing the negatively charged amino acid sequence Asp-Asp-Asp-Glu-Asp were obtained. Indirect immunofluorescence of the antigens recognized by the antibody was punctate at the nuclear rim or the nuclear surface, depending on the plane of focus. The antibody blocked transport of nuclear proteins into the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(42 citation statements)
references
References 26 publications
(7 reference statements)
3
39
0
Order By: Relevance
“…Antibodies against negatively charged polypeptides block the transport of SV40 T antigen into the nucleus in various cells, including mouse fibroblasts (Yoneda et al 1988). This suggests that wild-type SV40 T antigen may be transported to the nucleus by a charge-sensitive receptor molecule that recognizes a nuclear signal sequence on the T-antigen molecule.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibodies against negatively charged polypeptides block the transport of SV40 T antigen into the nucleus in various cells, including mouse fibroblasts (Yoneda et al 1988). This suggests that wild-type SV40 T antigen may be transported to the nucleus by a charge-sensitive receptor molecule that recognizes a nuclear signal sequence on the T-antigen molecule.…”
Section: Discussionmentioning
confidence: 99%
“…In rat liver, SV40 T antigen transport to the nucleus is mediated by an ATP-dependent active transport system (Markland et al 1987). Microinjection of antibodies raised against negatively charged peptides (Asp-Asp-Glu-Asp) inhibits nuclear transport of SV40 T antigen in a variety of cell lines (Yoneda et al 1988), suggesting that the cellular molecules involved in nuclear transport can be modulated experimentally. Deletion or mutation of the region of the T-antigen gene encoding the nuclear localization signal damages the capacity of mouse, hamster, and monkey cells to transport T antigen to the nucleus (Lanford andButel 1982, 1984;Kalderon et al 1984a, b;Alfano and McMacken 1989).…”
mentioning
confidence: 99%
“…Recently, Yoneda et al [33] suggested that the binding pocket of the putative nuclear signal receptor in nuclear pores contains numerous acidic residues that interact in a complementary fashion with the basic residues of the NLS sequence. They raised an antibody against a synthetic peptide, D-D-D-E-D, which is complementary to the NLS sequence of the SV40 large-T signal peptide and found that on microinjection into cultured cells, this anti-peptide antibody bound to nuclear envelopes and blocked NLS-mediated uptake of proteins into the nucleus.…”
Section: Acidic Amino Acid Clusters and Tyrosine Phosphorylation Sitementioning
confidence: 99%
“…binding proteins (Yoneda et al, 1988;Adam et al, 1989;Benditt et al, 1989;Li and Thomas, 1989;Lee and M616se, 1989;Silver et al, 1989) have also recently been identified, although their specificity and subcellular location remain unclear. It is well documented that the specificity of nuclear protein import is determined by the NLS .…”
mentioning
confidence: 99%